ANALISIS DAYA SAING PARIWISATA KOTA MALANG - Muflih, Muhammad Fadhlan; Ananda , Candra Fajri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The tourism industry is an important contributor to the economic success of a country. This is one of the supports in the development of tourism activities to become an important industry. Malang City interprets